P011 Preschoolers' Engagement with Screens: Time of Day and Associations with Sleep and Cognitive Development. (9th November 2022) - Axelsson, E; Paech, G; Metse, A
Abstract: Screen time is associated with poorer sleep in children, but there are calls for more evidence in the preschool years – a period of rapid cognitive and language development which are both influenced by sleep. The aim was to investigate preschool children's length of exposure to screen media and associations with sleep duration and sleep quality, but also screen content and times of day children engaged with screens. Associations with cognitive development were also assessed. The study was conducted with an online questionnaire completed by caregivers recruited via social media. Most children engaged with content of an entertaining nature. Half of the children engaged with screens during the day only and half both during the day and at night. Longer time engaged with screens was associated with shorter sleep duration and poorer sleep quality and this was regardless of time of day of engagement. Greater screen time also predicted lower communication and problem solving scores, and more attention difficulties, but sleep duration was not a significant predictor of cognitive outcomes. The findings indicate that preschoolers' engagement with screens has implications for their sleep even when engagement is predominantly occurring during the day. Greater screen time also has implications for cognitive development during a sensitive period. The findings raise questions about the time children spend on screens even during the day that could be spent on activities that better support sleep and development. Future studies with objective measures of sleep and direct measures of cognition with preschoolers are needed.